Consideration of non-valvular atrial fibrillation with left atrial appendage thrombus formation despite under appropriate oral anticoagulation therapy. (25th November 2020) - Shiraki, H; Tanaka, H; Yamashita, K; Tanaka, Y; Sumimoto, K; Shono, A; Suzuki, M; Yokota, S; Suto, M; Mukai, J; Takada, H; Matsumoto, K; et al.
Abstract: Background: Atrial fibrillation (AF) is the most frequently sustained cardiac arrhythmia, with a prevalence of about 2–3% in the general population. In accordance with CHADS2 or CHA2DS2-VASc score, appropriate oral anticoagulation therapy such as warfarin or direct oral anticoagulants (DOAC) significantly reduced the risk of thromboembolic events. However, left atrial (LA) thrombus can be detected in the LA appendage (LAA) in AF patients despite appropriate oral anticoagulation therapy. Purpose: Our purpose was to investigate the associated factors of LAA thrombus formation in non-valvular atrial fibrillation (NVAF) patients despite under appropriate oral anticoagulation therapy. Methods: We retrospectively studied consecutive 286 NVAF patients for scheduled catheter ablation or electrical cardioversion for AF in our institution between February 2017 and September 2019. Mean age was 67.1±9.4 years, 79 patients (29.5%) were female, and 140 (52.2%) were paroxysmal AF. All patients underwent transthoracic and transesophageal echocardiography before catheter ablation or electrical cardioversion. All patients received appropriate oral anticoagulation therapy including warfarin or DOAC for at least 3 weeks prior to transesophageal echocardiography based on the current guidelines. LAA thrombus was defined as an echodense intracavitary mass distinct from the underlying endocardium and not caused by pectinate muscles by at least three senior echocardiologists. Results: Of 286 NVAF patients with under appropriate oral anticoagulation therapy, LAA thrombus was observed in 9 patients (3.3%). Univariate logistic regression analysis showed that age, paroxysmal AF, CHADS2 score ≥3, left ventricular end-diastolic volume index (LVEDVI), left ventricular ejection fraction (LVEF), left ventricular mass index (LVMI), LA volume index (LAVI), mitral inflow E and mitral e' annular velocities ratio (E/e'), and LAA flow were associated with LAA thrombus formation. It was noteworthy that multivariate logistic regression analysis showed that LAA flow was independent predictor of LAA thrombus (OR: 0.72, 95% CI: 0.59–0.89, p<0.005) as well as LVEF. Furthermore, receiver operating characteristic (ROC) curve analysis identified the optimal cutoff value of LAA flow for predicting LAA thrombus as ≤15cm/s, with a sensitivity of 88%, specificity of 93%, and area under the curve (AUC) of 0.95. Conclusions: LAA flow was strongly associated with LAA thrombus formation even in NVAF patients with appropriate oral anticoagulation therapy. According to our findings, further strengthen of oral anticoagulation therapy or percutaneous transcatheter closure of the LAA may be considered in NVAF patients with appropriate oral anticoagulation therapy but low LAA flow, especially <15cm/s. Funding Acknowledgement: Type of funding source: None